2-dimensional materials-based electrical/optical platforms for smart on-off diagnostics applications. (10th June 2020) - Kou, Jing; Nguyen, Emily P.; Merkoçi, Arben; Guo, Zhenzhong
Abstract: The concept of two-dimensional (2D) materials was first proposed after the first successful separation of graphene, a monoatomic layered material. 2D materials are referred to materials in which electrons can only move freely on the nanoscale in two dimensions, and have expanded to also include the transition metal dichalcogenides (TMDs), black phosphorus (BP) and hexagonal boron nitride (hBN). Different 2D materials have unique electrical or optical characteristics due to the special properties of the crystal structure, and are widely used as field-effect transistors and optoelectronic devices. Moreover, based on the electrochemical and fluorescence quenching properties, many researchers have developed and fabricated light-switching and current-switching sensors for various medical diagnostics. In this paper, we summarize the characteristics of 2D materials and introduce their photoelectric properties, and review the recent applications of 2D materials based switching sensors for the diagnosis of various diseases.